Ngudari reribet in a woman survivor of depression during the Covid-19 pandemic - Sugiarto, Ryan; Sundari, Any (Universitas Muhammadiyah Surakarta, 2022)
Abstract. This study aims to explore the experiences of depression survivor during the COVID-19 pandemic to cope with depression. This study used a grounded theory approach, with a single subject who until this research was completed in the recovery phase from depression. The subject was selected for the first reason, she had been diagnosed to experience anxiety and depression and was still in the recovery stage. Second, the subject learned and practiced Kawruh Jiwa Ki Ageng Suryomentaram to help her recover from anxiety and depression. The data collection method used was a semi-structured interview, which was conducted four times, recorded, and transcribed verbatim. Data were analyzed using coding by processing basic data into conceptual data. The results of this study indicated that: 1) the pandemic is a common trigger factor that causes the subject to feel depressed; 2) grief because of the death of both parents is the leading trigger for the subject to experience anxiety and depression. Subject experienced 10 of 17 signs of depression both in aspects: Motor, autonomic hyperactivity, excessive alertness, and reduced apprehension.Research also showed that efforts to ngudari reribet (solving problems of anxiety and depression) are performed in several stages: First, kandha takon both interpersonally (sharing) with others by seeking help from professionals, psychologists, and psychiatrists and kandha takon with an intrapersonal model (nyawang karep), second, nyocoaken raos by examining feelings what she feels herself, the three jawah kawruh (understanding and perceiving the feeling she feels herself ), the four Aku, sak iki, nengkene, ngene, gelem accepting herself today, and mawas diri, introspective efforts to keep her consciousness intact. These findings open up a new space to build the discourse and practice of psychological therapy in anxiety and depression survivors. Keywords: depression; Covid-19; ngudari reribet; woman